ARTS THERAPIES IN LIFELONG LEARNING – OPPORTUNITIES AND SOLUTIONS - Stiegele, Dace; Paipare, Mirdza (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Observing lifelong learning programs in Latvia, there is a tendency to develop study courses that ensure the acquisition of new professional knowledge and skills, as well as their development, but a very minor section of courses and programs is devoted to the personality, resources, needs and acquisition of broad skills involved in adult education.In professional and scientific literature there is no reflection of the research conducted so far in Latvia on the use of arts therapies in maintaining the quality of life of adults in the context of lifelong learning.Purpose of the article: to research education as one of the indicators of quality of life in Europe and Latvia and differences and similarities in andragogy and arts therapies in order to get an idea of the possibilities of using arts therapies in lifelong learning.Method: content analysis of pedagogical and psychological literature, scientific articles, data of Eurostat population quality of life surveys, as well as official EU and Republic of Latvia guidelines on quality of life and lifelong learning issues.Results: the professional and personal competencies of an adult educator and an art therapist are highly demanding and have a number of common features. An adult educator and an art therapist have similar professional tasks - to see the needs of those involved in adult education and arts therapies, to support individual self-development, to encourage personality development, thus improving the quality of life. For each specialisation of arts therapies (music, dance and movement, drama and visual plastic) a specific application can be made according to target groups, educational stage and programs, as well as areas of needs.